Civil-Law Education: Foreign and Russian Experience - Malevanov, Evgeny Y.; Novoselova, Svetlana Y.; Bolotina, Tatyana B.; Pevtsova, Elena A.; Tikhonov, Andrey I. (International Review of Management and Marketing, 2016)
The relevance of the study is conditioned by the peculiarities of civil-law education in contemporary society and the necessity to form a coherent civil and legal educational system for social problems' effective solving. The purpose of this article is to identify the effective core directions of youth civil-law education in the contemporary world in the context of the study of national and international experience, as well as to offer the most effective model of civic education. The leading methods of this problem's study are the methods of philosophical cognition (dialectical, historical- logical, systematic -analytical methods), allowing in the complex to take into consideration the subject of research. The article reveals the basic characteristics of civil law education in Russia and abroad, presents a model to assess the quality of civic and law education, justifies patriotic education's approaches in Russia and foreign countries, reveals core directions for the development of civic education in the context of domestic and foreign practice. The structure of the considered practical educational model that embodies the internationalization paradigm can be the basis to build innovative educational curricula that do not possess an absolute national and regional insularity, but include the leading invariant components of Western educational standards relating primarily to the complex of general subjects, aimed at the formation of the civil and law activity of a modern person. Keywords: civil society, the scope of public relations, civil - law relations, socio-law education, modern educational paradigm. JEL Classifications: A23, I23, I26